Osmium tetroxide-(QN)(2)PHAL in an ionic liquid: a highly efficient and recyclable catalyst system for asymmetric dihydroxylation of olefins - Song, CE; Jung, DU; Roh, EJ; Lee, SG; Chi, DY (ROYAL SOC CHEMISTRY, 2002)
In Os-catalysed asymmetric dihydroxylation using NMO as a co-oxidant, the combination of an ionic liquid and the new bis-cinchona alkaloid 2 generated in situ from (QN)(2)PHAL during reaction provided a simple and practical approach to the recycling of both catalytic components (osmium tetroxide and chiral ligand).